Temporal changes in the incidence of ductal carcinoma in situ in Goiânia, Brazil: a population-based study - Nayara Alves de Freitas, Lemos; Junior, Ruffo Freitas; Carleane Maciel Bandeira, Silva; Marise Amaral Rebouças, Moreira; de Paula, Élbio Candido; Maya Aires Freitas, Nilceana; Martins, Edesio; Carlos de Oliveira, José; Maciel Reis Gonzaga, Carolina; Borges, Marcus Nascimento; Junior, Julio Roberto Macedo Bernardes; Savaris, Ricardo Francalacci; et al. (Mastology, 2025)
Mammography screening has resulted in a considerable increase in the diagnosis of early-stage tumors in various countries. However, most available data refer to high-income countries, hospital-based studies, or studies with limited follow-up. Therefore the aim of this study was to determine the incidence of ductal carcinoma in situ (DCIS) in Goiânia, Brazil. Methods: Ecological study among residents of the city of Goiânia, Brazil. We included all the DCIS cases registered at the Goiânia population-based cancer registry between 1994 and 2010. Crude incidence and age-standardized incidence rates (using the world standard population) were calculated. Poisson regression was used to analyze temporal changes, with the average annual percent change (AAPC) in the crude and age-standardized incidence rates being calculated. Results: There were 261 cases of DCIS, with an annual incidence rate that ranged from 0.58 to 4.21 per 1,000 women (crude and standardized) over the period. The number of cases of DCIS in the 40–49 and 60–69-years age groups increased significantly (p<0.01). The AAPC of the crude incidence rate for the period was 11.88% per year (95%CI 9–15; p<0.01) and the standardized rate was 11.89% per year (95%CI 9–15; p<0.01).